2012
DOI: 10.1126/science.1224763
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Homogeneous Nucleation During the Melting of Superheated Colloidal Crystals

Abstract: The nucleation process is crucial to many phase transitions, but its kinetics are difficult to predict and measure. We superheated and melted the interior of thermal-sensitive colloidal crystals and investigated by means of video microscopy the homogeneous melting at single-particle resolution. The observed nucleation precursor was local particle-exchange loops surrounded by particles with large displacement amplitudes rather than any defects. The critical size, incubation time, and shape and size evolutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
172
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 36 publications
8
172
0
Order By: Relevance
“…In order to gain a better fundamental understanding of how to control self-assembly processes in the fabrication of novel structures, many experimental and simulation studies have been devoted to colloidal systems. Experiments [1][2][3][4] and computer simulations [5][6][7] on bulk hard-sphere colloids suggested that the metastable fluid crystallizes and superheated crystals melt via a single-step nucleation process that is well described by classical nucleation theory (CNT) [8]. However, Ostwald's step rule suggests that the kinetic pathway to the most stable state can initially proceed through the nucleation of intermediate, metastable phases [9].…”
mentioning
confidence: 99%
“…In order to gain a better fundamental understanding of how to control self-assembly processes in the fabrication of novel structures, many experimental and simulation studies have been devoted to colloidal systems. Experiments [1][2][3][4] and computer simulations [5][6][7] on bulk hard-sphere colloids suggested that the metastable fluid crystallizes and superheated crystals melt via a single-step nucleation process that is well described by classical nucleation theory (CNT) [8]. However, Ostwald's step rule suggests that the kinetic pathway to the most stable state can initially proceed through the nucleation of intermediate, metastable phases [9].…”
mentioning
confidence: 99%
“…Perhaps, the introduction of a balanced dynamics, considering not only the T2 processes but also coalescence with vanishing GBs would be beneficial to those models. Experimentally, colloidal particles have shown to be a useful model system where to probe atomistic phenomena [3][4][5][6][7]. Their large size (∼µm) and slow motion (∼s) allow us to use simple optical techniques, like video microscopy, to study the crystallization phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this is the possibility to adjust the interaction potential between the particles by chemically modifying their surfaces, which would allow us to study the many different structures obtained by self-assembly. Another important reason is the capability of researchers to study the crystallization process by direct observation with simple laser diffraction and optical video microscopy, given that their size and interparticle distance is usually comparable to the wavelength of visible light and that their dynamics is slow enough to follow the trajectories of the individual particles [3][4][5][6][7]. Last but not least in importance is the possibility of applying some of the colloidal crystalization results to the self-assembly of proteins in their native globular state, a topic with the utmost attention paid in recent years; although in this case, by their very nature, the interaction between the proteins is not isotropic as with spherical colloidal particles, which enriches but complicates the problem [8].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the rate of growth of particles can be deduced when one takes several TEM images as a function of time. Figure 4 shows that the growth rate decreases through the first two seconds (from 13 nm/s down to 0.14 nm/s) [12]. This is followed by a constant growth rate 0.034 nm/s when time reaches high values (20 seconds).…”
mentioning
confidence: 94%